LEGAL REVIEW OF MURDER THROUGH 'SANTET' IN THE LEGAL PERSPECTIVE OF INDONESIA (A STUDY OF LAW NO. 1 OF 2023 REGARDING 'SANTET') - Gunawan Nachrawi; Sukamto Kusnadi (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
: "Santet" is one of Indonesia's cultural legacies that draws the attention of many communities due to its invisible movements, yet its impacts can inflict suffering on an individual's mental and physical well-being. Typically, the perpetrator sends "santet" to someone fueled by resentment, which subsequently fosters hatred, ultimately leading them to consult a shaman to cast a curse on the disliked individual. It is not uncommon for a person to lose their life as a result of being cursed. "Santet" is generally believed to be an act capable of causing harm to an individual through mystical means. The harm caused by "santet" can be directly observed on the victim but is challenging to explain medically. In various cases, it is common for the victim to experience unexplained pain or wounds due to foreign objects inside their body, although the origin of these foreign objects cannot be medically accounted for. These foreign objects can be nails, iron, needles, hair, or other sharp items. In extreme cases, "santet" can even lead to death, causing public concern over deaths that are difficult to legally attribute to curses. Murder through "santet" is considered difficult to prove materially, rationally, and logically, despite numerous cases of such instances occurring in various communities. Murder is inherently illegal; however, the use of "santet" as a means of committing murder cannot be substantiated as a concrete basis for legal proof. Law No. 1 of 2023 only regulates individuals or shamans who admit to possessing knowledge of "santet" and must meet specific criteria outlined in Article 252 of the Indonesian Penal Code (KUHP) in their practice of casting curses. The Indonesian legal system, based on formal and rational principles, processes actions that are concrete in nature, possess distinct characteristics, and can establish cause and effect relationships. The act of performing "santet" is far removed from human comprehension and is challenging to accept within the formal legal framework and prove concretely. "Santet" itself is a facet of black magic that is believed to persist. From ancient times to the present, the intent and purpose behind those who practice "santet" are usually negative, aiming to harm, destroy, or cause damage. This is achieved by inserting objects into the victim's body with the assistance of supernatural beings such as spirits and demons. Article 252, Paragraph (1) of the Indonesian Penal Code, stipulated in Law No. 1 of 2022, imposes criminal penalties for those who engage in "santet," with a potential sentence of up to 1.5 years. Philosophically, "santet" can be classified as a criminal act due to its recognition and belief in its existence within society, leading to distress and harm. However, it cannot be prevented or eradicated through legal means, as "santet" is abstract and its legal proof presents challenges within the Indonesian legal system.